Giant Cell Tumor of the Temporal Bone Invading into the Pterygoid Muscle through the Temporomandibular Joint - Mohamed, Aboshanif; Ishikawa, Kazuo; Omi, Eigo; Honda, Kohei; Suzuki, Shinsuke; Sato, Teruyuki; Fukui, Naoko; Takahasi, Masataka (Journal of Neurological Surgery Reports, 2014)
We report a case of giant cell tumor of the temporal bone invading into the pterygoid muscle through the temporomandibular joint. The patient was a 43-year-old woman who developed left ear fullness 2 years earlier with a mass in the external auditory canal. Radiologic evaluation revealed extension into the infratemporal fossa and confirmed that the tumor was invading into pterygoid muscle. A middle cranial fossa approach along with tympanoplasty was used for total resection of the tumor. Once a tumor invades into muscle tissue, meticulous care is required to remove it because identification of tumor tissue becomes extremely difficult.
Keywords: giant cell tumor; temporal bone; pterygoid muscle; temporomandibular joint